2007
DOI: 10.1029/2006jd007114
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of anthropogenic aerosols on regional precipitation over east Asia

Abstract: [1] A regional coupled climate-chemistry-aerosol model is developed. It is used to assess the direct and indirect effects of anthropogenic sulfate and carbonaceous aerosols on regional climate over east Asia with a focus on precipitation. The simulated direct and first indirect effects for the most part reduce the solar radiation and hence decrease the surface temperature, while the second indirect effect generates both negative solar forcing and a substantial positive long-wave forcing. It decreases the preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
101
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 100 publications
(225 reference statements)
12
101
1
1
Order By: Relevance
“…Regional sulfate forcing from GCCM reaches In East Asia for example, weaker summer monsoon and stronger winter monsoon emerge under the forcing of anthropogenic sulfate, leading to reduced moisture flux from the ocean to the East Asian continent in both seasons. The changes are in many aspects similar to those simulated with the regional coupled climate-chemistry model by Huang et al (2007) who found regional radiative forcing and surface cooling in East Asia (note: area definition might be different from ours) to be −4.08 W m −2 and −0.35 K, respectively. They also found a reduction of cloud fraction by 0.8% and precipitation by more than 10%; whereas the values from GCCM (2.4%, and 10.3%, respectively) are of similar orders.…”
Section: Climate Responses To Sulfate Forcingsupporting
confidence: 56%
See 1 more Smart Citation
“…Regional sulfate forcing from GCCM reaches In East Asia for example, weaker summer monsoon and stronger winter monsoon emerge under the forcing of anthropogenic sulfate, leading to reduced moisture flux from the ocean to the East Asian continent in both seasons. The changes are in many aspects similar to those simulated with the regional coupled climate-chemistry model by Huang et al (2007) who found regional radiative forcing and surface cooling in East Asia (note: area definition might be different from ours) to be −4.08 W m −2 and −0.35 K, respectively. They also found a reduction of cloud fraction by 0.8% and precipitation by more than 10%; whereas the values from GCCM (2.4%, and 10.3%, respectively) are of similar orders.…”
Section: Climate Responses To Sulfate Forcingsupporting
confidence: 56%
“…Shindell et al (2001) also used online model to illustrate that the OH concentration could be reduced by about 10%, which would be significant to many chemical processes. Besides global models, regional models are also tending towards online coupling (e.g., Giorgi et al 2002;Grell et al 2005;Forkel and Knotche 2006;Huang et al 2007), as the radiative effects can be particularly strong on the local scales.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of aerosol chemical composition and aerosol optical depth in the Nepal Himalaya have clearly shown the build up of aerosols in the pre-monsoon season during the winter and early spring, with relatively high values of light absorbing particulate matter including dust and black carbon (Carrico et al, 2003). Very recently, new insight into the mechanisms of aerosol transport from dust and pollutions sources in central and southeastern Asia to the Tibetan and Himalayan regions was also provided by Huang et al, 2007 andRamanathan et al, 2007. These studies indicate that aerosol in-situ and columnar concentrations over the south slope of Himalayas are strongly affected by the development of the boundary layer, responsible for transporting pollution aerosols upward, contributing to changes in solar irradiance Dumka et al, 2008;Ramachandran, 2008). Assessing the impact of aerosol particle on the local energy balance in the high altitude regions of Himalayas is therefore of importance for the whole area of HKH regions.…”
mentioning
confidence: 99%
“…Subsequently, however, this cold and dry anomaly is advected into Asia, where it induces atmospheric and surface feedbacks over Asia and the Western North Pacific (WNP), which also weaken the EASM. In spite of very different perturbations to the local aerosol burden in response to Asian and European sulphur dioxide 1 3 , decadal changes in sensible heat flux over the Tibetan Plateau (Ding et al 2009;Duan et al 2013), anthropogenic aerosol (Xu 2001;Menon et al 2002;Huang et al 2007;Liu et al 2009Liu et al , 2011Chen et al 2012;Zhang et al 2012;Guo et al 2013;Hwang et al 2013;Jiang et al 2013;Ye et al 2013;Wang et al 2013;Zhou et al 2013;Polson et al 2014;Song et al 2014), and natural decadal variability (Lei et al 2011).…”
Section: Introductionmentioning
confidence: 99%